2023
DOI: 10.1021/acsanm.2c05575
|View full text |Cite
|
Sign up to set email alerts
|

Non-Uniformly Strained Core–Shell InAs/InP Nanowires for Mid-Infrared Photonic Applications

Abstract: Crystal phase and strain engineering in epitaxial nanowire (NW) heterostructures provide a widely tunable functionality for future nanoscale light emitters and photodetectors. Thus, InAs band gaps can be finely tuned in the midinfrared range by introducing a mechanical strain through lattice mismatch in core−shell NWs. Here, we demonstrate that the inhomogeneity of the InP shell thickness leads to a non-uniform stress field and a local variation in the degree of surface passivation along the InAs NW length whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…As reported in refs , , self-induced grown InAs NWs possess a high stacking fault density along the (0001) growth direction. High-resolution transmission electron microscopy (HRTEM) studies of individual NWs revealed that the presence of a nitrogen flux during NW MBE growth does not significantly alter the density or type of the observed defects.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…As reported in refs , , self-induced grown InAs NWs possess a high stacking fault density along the (0001) growth direction. High-resolution transmission electron microscopy (HRTEM) studies of individual NWs revealed that the presence of a nitrogen flux during NW MBE growth does not significantly alter the density or type of the observed defects.…”
Section: Resultssupporting
confidence: 65%
“…As shown in refs , , a random distribution of stacking faults can result in a red shift of the PL emission compared to the WZ band gap value (see Section S4 in the Supporting Information). Consequently, the PL emission maxima of the pristine InAs NWs at 437 meV lie between the theoretical band gap values of ZB (415 meV) and WZ (477 meV) InAs phases (marked by red and blue vertical lines, as shown in Figure a, respectively).…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations